Disputed aspects of the reputation management implementation - Vitaliy Shkromyda (Journal of Vasyl Stefanyk Precarpathian National University)
The recognition of the company and its products, its positive perception among stakeholders are important drivers of sustainable development, which together generate constant sales, provide high margins and strengthen competitive positions in the relevant market. The key factor in this success is the company’s impeccable corporate reputation, the importance and role of which is more and more attested by the researchers in their publications, both on the theoretical and practical levels.